Scheme Exploration and Performance Analysis of 800-Meter Superlarge Span Structure - Deshen Chen; Hongliang Qian; Huajie Wang; Yue Wu (Advances in Civil Engineering)
Superlarge span structure is one of the important trends for future building development. Under the background of the 800-meter superlarge span dome project proposed by China Construction Group, this paper focuses on the structural optimization and performance analysis of this superlarge span structure. The previous ideas of the superdome and the maximum span of existed spatial structures are reviewed, and some structural form selection principles are put forward which lay foundation for structural selection. The applicability of high-strength steel and aluminum alloy is also discussed. It is demonstrated that the high-strength steel and aluminum alloy contribute little to structural comprehensive performances. Then, considering the effects of grid division, members topological relation, and surface shape, six kinds of rigid systems are contrastively studied to determine the optimal scheme. The structural performances along with the increasing span are explored in detail. To further reduce the structural weight and improve mechanical performance, a new composite scheme and the cable-stayed megastructure are proposed and studied. The research methods and performance analysis results can provide significant references for the following research on the superlarge span structure.